Prevalance and clinical importance of some pathogen microorganisms found in the cervix of women who apply for voluntary abortion - Açik, Yasemin; Güngör, Leyla; Aşçi Toraman, Zülal (My University, 2004)
Objective: Pelvic inflammatory disease (PID) is an important complication of termination of pregnancy by abortion. This study intends to determine the prevalance of some pathogen microorganisms that are found in the cervix of women who apply for voluntary abortion that can lead to PID. Materials and Methods: The subjects of this study are 60 women who applied to Elazi? State Hospital, Family Planning Polyclinics (ESHFPP) between 02.03.2001 - 20.04.2001 for voluntary abortion and who have not taken any antibiotics before abortion. Upon examination, women with undesired pregnancy up to 10 months were given an appointment for the next day, and recommended to come without making vaginal lavage. Before examining the women, dry sterile speculum was applied, vaginal and cervical samples taken, and promptly cultured. Results: Average age of the women covered by the study is 30.7 ± 5.3 years. Reproduction was observed on 78.3% of the cultures taken. In 25.0% of the cultures, C. trachomatis, and N. gonorrhoeae developed which are considered to carry high risk for PID; in 86.7%,. G. vaginalis, C.albicans, Group B streptococcus, E.coli, and T.vaginalis which carry medium risk developed. More than one positive microorganisms were observed in the materials taken from 25% of the patients. Conclusion: Pathogen microorganisms developed in materials of most of the women who applied to ESHFPP for voluntary abortion. Therefore we conclude that examination for cervical and vaginal pathogens is necessary in patients who apply for voluntary abortion.
İste?e ba?li düşük yapmak i?çi?n başvuran kadinlarin servi?ksi?nde bulunan bazi patojen mi?kroorgani?zmalarin prevalansi ve kli?ni?k önemi?
Keywords: Abortion; Cervix; Microorganisms; Prevalance